Analysis of Environmental Performance and Tax Aggressiveness on CSR Disclosure: A Study of PROPER KLH Companies in the Indonesian Sharia Stock Index 2017-2022 - Ahmad Rizqi Makinudin; Ali Rama; Zuhairan Yunmi Yunan (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
This study investigates the factors influencing Corporate Social Responsibility (CSR) disclosure among companies listed in the PROPER KLH within the Indonesian Sharia Stock Index (ISSI) from 2017 to 2022. Utilizing a quantitative approach, the research employs secondary data and panel data regression analysis. The results reveal that environmental performance, company age, and tax aggressiveness significantly affect CSR disclosure, as measured by the Global Reporting Initiative (GRI) index. These findings underscore the crucial role of these factors in shaping a company's commitment to social and environmental responsibilities, while also highlighting the complex dynamics between corporate actions and their environmental impact. Companies with strong environmental performance not only contribute positively to the planet but also enhance their long-term reputation. The relationship between tax aggressiveness and CSR disclosure suggests a significant interplay between financial strategies and ethical considerations in corporate decision-making. This underscores the need for a comprehensive approach to corporate governance that integrates financial objectives with ethical responsibilities. Consequently, policymakers and stakeholders should leverage these insights to develop more effective regulations and incentives that promote responsible corporate conduct.